Microbes, macrophages, and melanin: a unifying theory of disease as exemplified by cancer - Berg, Stacie Z.; Berg, Jonathan (Frontiers in Immunology, 2025)
It is widely accepted that cancer mostly arises from random spontaneous mutations triggered by environmental factors. Our theory challenges the idea of the random somatic mutation theory (SMT). The SMT does not fit well with Charles Darwin’s theory of evolution in that the same relatively few mutations would occur so frequently and that these mutations would lead to death rather than survival of the fittest. However, it would fit well under the theory of evolution, if we were to look at it from the vantage point of pathogens and their supporting microbial communities colonizing humans and mutating host cells for their own benefit, as it does give them an evolutionary advantage and they are capable of selecting genes to mutate and of inserting their own DNA or RNA into hosts. In this article, we provide evidence that tumors are actually complex microbial communities composed of various microorganisms living within biofilms encapsulated by a hard matrix; that these microorganisms are what cause the genetic mutations seen in cancer and control angiogenesis; that these pathogens spread by hiding in tumor cells and M2 or M2-like macrophages and other phagocytic immune cells and traveling inside them to distant sites camouflaged by platelets, which they also reprogram, and prepare the distant site for metastasis; that risk factors for cancer are sources of energy that pathogens are able to utilize; and that, in accordance with our previous unifying theory of disease, pathogens utilize melanin for energy for building and sustaining tumors and metastasis. We propose a paradigm shift in our understanding of what cancer is, and, thereby, a different trajectory for avenues of treatment and prevention.